Contribution to Informal Economy; Voice of Women Artisans of India - Mehta, Maahi A. (Integrated Journal for Research in Arts and Humanities, 2024)
Art is not just a part of life; for some, it’s life itself! and this life is being lived to the fullest by the women artisans who not only nourish the art like their own kin but also help in promoting the GDP and shaping the economy of the country. According to the International Trade Centre, women make up for 70% of the global handicraft workforce. Here, through this exhaustive research, we shall analyze the contributions, challenges, solutions and outcomes of the voice of women artisans in India and how In- dia’s GDP has got a boost indirectly with women artisans taking the center stage. A KPMG study estimated that approximately 7.3 million people depend on handicraft and allied activities for livelihood. The handicraft and handloom sector in India is a Rs 24,300-crore industry and contributes nearly Rs 10,000 crore annually in export earn- ings. Women Artisans of India and the tribal communities gearing up with their act is tru- ly inspiring amidst the brand market of the world where handmade threads and knots are giving a run for the money to the machine made and robotic assembled goods. Vocal for local and its impact which not only promotes self reliability in the tourism sec- tor but even sustainability and is environment friendly is another feature that is touched upon with reference to Indian handicrafts and emergence of new startups promoting an-cient Indian techniques is another interesting feature. Self help group and NGOs sup- porting the economic development especially during the COVID pandemic times where this industry was the worst hit has been he life savior of this massive Industry. Digital empowerment ensuring higher market reach and faster market capture is the tool that does the trick with women artisans voicing in their concerns and asking for a leading hand not for their support from the masses but an indirect upliftment via awareness generated in the market. This awareness is the gateway to Education.